Legal Analysis Of Binary Options Through Online-Based Platforms - Ardiansyah, Muhammad; Prastyo, Brian Amy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The fraudulent acts that are currently taking place are important to be studied, discussed, and investigated because these violations are now easier to carry out. This study aims to analyze related to the legal rules governing binary options trading platform online considering the rules and regulations enforced in Indonesia, and regarding legal protection and the role of the government related to binary options trading carried out on an online platform in Indonesia. This research uses regulatory research with a legal methodology. The method of collecting information is through meetings and written studies with subjective investigation procedures. The result of this research is the legal aspect of trading binary options activities carried out in Indonesia, namely that binary options are illegal activities, this is because the platform has no legality and has been blocked by Bappebti as part of the Investment Satgas Waspada Investasi (SWI), Bappebti regularly checks and pays attention, especially to futures trading products that do not have a license from Bappebti